The inventory of the Portuguese geological heritage: a good example of scientific cooperation between universities - Pereira, Paulo (2012)
The first systematic inventory of the Portuguese geological heritage is a clear example of the academic collaboration that characterizes the geoconservation in Portugal. Three hundred and twenty six geosites with inter- national or national relevance have been inventoried under the scope of the scientific research project “Identifica- tion, characterisation and conservation of geological heritage: a geoconservation strategy for Portugal”. The geosites were selected exclusively based on their scientific value and support twenty-seven frameworks. For each geological framework a leading geoscientist from a university was responsible for the scientific characterization of the framework, to invite collaborators to identify representative geosites, and to assess the scientific value and vulnerability of the geosites. In the end, seventy geoscientists, mainly from universities, took part in the scientific results that are now important raw data to support nature conservation initiatives.